Investigation of bovine serum albumin aggregation upon exposure to silver(i) and copper(ii) metal ions using Zetasizer - Alhazmi Hassan A. (De Gruyter, 2021)
Depending upon the metal coordination capacity and the binding sites of proteins, interaction between metal and proteins leads to a number of changes in the protein molecule which may include the change in conformation, unfolding, overall charge, and aggregation in some cases. In this study, Cu(ii) and Ag(i) metal ions were selected to investigate aggregation of bovine serum albumin (BSA) molecule upon interaction by measuring the size and charge of the aggregates using nano-Zetasizer instrument. Two concentrations of metal ions were made to interact with a specific concentration of BSA and the size and zeta potential of BSA aggregates were measured from 0 min upto 18 h. The Cu(ii) and Ag(i) metal ions showed almost similar behavior in inducing the BSA aggregation and the intensity of peak corresponding to the normal-sized protein decreased with time, whereas the peak corresponding to the protein aggregate increased. However, the effect on zeta potential of the aggregates was observed to be different with both metal ions. The aggregation of protein due to interaction of different metal ions is important to study as it gives insight to the pathogenesis of many neurological disorders and would result in developing effective ways to limit their exposure.